Common paediatric surgical problems in Bangladesh: experience in tertiary care center, Dhaka, Bangladesh - Shahjahan, M.; Elahi, Khondaker M.; Nrjana, Nusrat J.; Islam, M. Kabirul (International Journal of Contemporary Pediatrics, 2024)
Background: There are several challenges at the global and national levels that contribute to surgery in children’s health. The aim of the study was to evaluate the surgical problems in children in Dhaka Shishu Hospital-that is in Bangladesh. Methods: This retrospective study was carried out in the department of pediatric surgery, Dhaka Shishu Hospital. A retrospective study of surgical problems in children’s in the last 10 (September 2013 to October 2023) years were done in admitted patients in the surgery department. A total of 12689 patients were participated in the study. The surgical units of this hospital contain 100 beds. So, the average total number of surgical patients are 200. This is for the first time in our country an attempt is made to present a data of surgical problems in children’s in Bangladesh in the experience of Dhaka Shishu Hospital. Statistical analyses of the results were obtained by using statistical packages for social sciences (SPSS-24). Results: A total number of 12689 patients; aged <10 years; admitted in the surgical units of Dhaka Shishu Hospital in the last 10 years were reviewed. Male patients were 59%, female 42%. Among them 29% were of age below 1 year, 43% from 1 to 5 years and 29% were above 5 years. Gastro-intestinal disorders were the commonest problem observed-constituting 43.9% of cases, while 9.2% of children came with burn injury. Conclusions: The management of surgical problems often requires a multidisciplinary approach and advancements in surgical techniques, anesthesia, and perioperative care have improved the surgical interventions in pediatric patients over the years.